Estrategia didáctica basada en la interrogación en el cuidado del cuerpo y conservación de la salud en los niños/as de 5 años de la I.E N°083 Tahuantinsuyo - Cabanillas Valdez, Gloria (2012)
The didactic based strategy in the immersed interrogation in present investigation, you are born for the sake of improving the care of the body and conservation of the health in the boys and girls of five years, justified for your convenience, social relevance, benefit metodológica, practica! benefit and feasibility. lt was necessary to turn to fact-finding background and theoretic contributions for your realization, the same that they allowed formulating and to contrast the factfinding hypothesis: lf it becomes elaborate and the didactic based strategy in the interrogation is applied then the care of the body and the l's conservation of the health in the boys and girls of five years are improved significantly. E. N 083 - Tahuantinsuyo, of the district Nueva Cajamarca. The study fits to the kind of applied investigation, experimental patterned level experimental pre, whose coverage comprises the boys and girls of five years and 20 boys and girls's sign; Whom they administrated two observations to to them: In order to diagnose the dangerous level of the body and conservation of the health before the application of strategy and a second observation to determine the influence of the strategy after your application. For the anthology of the data of the sign of study, a fiche of observation with 20 items was used. The obtained data were processed in electronic intervening form the Software SPSS v17 and checkered presentees and graphics constructed according to standards established for investigation. Right after interpretation, analysis and discussion of the results, the alternative hypothesis signifying was accepted than the application of the didactic, based strategy in The interrogation, the N has improved the care of the body and the Educational lnitial lnstitution's conservation of the health in the boys and girls of five years significantly 083 of the sector Tahuantinsuyo, of the district of Nueva Cajamarca.